Patients' and kidney care team's perspectives of treatment burden and capacity in older people with chronic kidney disease: a qualitative study. Issue 12 (12th December 2020) - Hounkpatin, Hilda O; Leydon, Geraldine M; Veighey, Kristin; Armstrong, Kirsten; Santer, Miriam; Taal, Maarten W; Annells, Pete; May, Carl; Roderick, Paul J; Fraser, Simon DS
Abstract : Objective: Chronic kidney disease (CKD) is often a multimorbid condition and progression to more severe disease is commonly associated with increased management requirements, including lifestyle change, more medication and greater clinician involvement. This study explored patients' and kidney care team's perspectives of the nature and extent of this workload (treatment burden) and factors that support capacity (the ability to manage health) for older individuals with CKD. Design: Qualitative semistructured interview and focus group study. Setting and participants: Adults (aged 60+) with predialysis CKD stages G3–5 (identified in two general practitioner surgeries and two renal clinics) and a multiprofessional secondary kidney care team in the UK. Results: 29 individuals and 10 kidney team members were recruited. Treatment burden themes were: (1) understanding CKD, its treatment and consequences, (2) adhering to treatments and management and (3) interacting with others (eg, clinicians) in the management of CKD. Capacity themes were: (1) personal attributes (eg, optimism, pragmatism), (2) support network (family/friends, service providers), (3) financial capacity, environment (eg, geographical distance to unit) and life responsibilities (eg, caring for others). Patients reported poor provision of CKD information and lack of choice in treatment, whereas kidney care team members discussed health literacy issues. Patients reported having to withdraw from social activities and loss of employment due to CKD, which further impacted their capacity. Conclusion: Improved understanding of and measures to reduce the treatment burden (eg, clear information, simplified medication, joined up care, free parking) associated with CKD in individuals as well as assessment of their capacity and interventions to improve capacity (social care, psychological support) will likely improve patient experience and their engagement with kidney care services.